Adaptive Pulvinar Circuitry Supports Visual Cognition. Issue 2 (February 2016) - Bridge, Holly; Leopold, David A.; Bourne, James A.
Abstract : The pulvinar is the largest thalamic nucleus in primates and one of the most mysterious. Endeavors to understand its role in vision have focused on its abundant connections with the visual cortex. While its connectivity mapping in the cortex displays a broad topographic organization, its projections are also marked by considerable convergence and divergence. As a result, the pulvinar is often regarded as a central forebrain hub. Moreover, new evidence suggests that its comparatively modest input from structures such as the retina and superior colliculus may critically shape the functional organization of the visual cortex, particularly during early development. Here we review recent studies that cast fresh light on how the many convergent pathways through the pulvinar contribute to visual cognition. Trends: The pulvinar plays a critical role in the early development of the primate dorsal visual stream, relaying visual information directly from the retina to the cortex before the more prominent pathway through the lateral geniculate nucleus to the primary visual cortex (V1) is fully mature. Abnormal retention of this early visual pathway through the pulvinar may explain the preservation of vision when lesions to V1 occur during infancy. In the adult, subcortical and cortical signals converge in multiple pulvinar subdivisions, although there is minimal evidence that the information from the two sources is actively integrated. Most research on the human pulvinar has been directed toward attention and emotional processing, although it is hypothesized to have a broader role in human cognition.